Lifetime Autism Spectrum Features in a Patient with a Psychotic Mixed Episode Who Attempted Suicide. (30th September 2014) - Simoncini, Marly; Miniati, Mario; Vanelli, Federica; Callari, Antonio; Vannucchi, Giulia; Mauri, Mauro; Dell'Osso, Liliana
Abstract : We present a case report of a young man who attempted suicide during a mixed episode with psychotic symptoms. The patient's history revealed the lifetime presence of signs and features belonging to the autism spectrum realm that had been completely overlooked. We believe that this case is representative of an important and barely researched topic: what happens to children with nondiagnosed and nontreated subthreshold forms of autism when they grow old. The issue of early recognition of autism spectrum signs and symptoms is discussed, raising questions on the diagnostic boundaries between autism and childhood onset psychotic spectrums among patients who subsequently develop a full-blown psychotic disorder.